Land ordering in the land communities of Dniper Ukraine in 1922–1930 - Kalinichenko, Viacheslav (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2022)
Research aim. To analyze the process of land management and land management in the land communities of Dnieper Ukraine in the 1920s. Methodology of the research. The research used general scientific and special historical methods. The study of historiography required the use of methods of analysis, synthesis, generalization, and classification. The use of the statistical method made it possible to obtain generalized indicators, to study the dynamics and changes in the process of land management. The study of minutes of general meetings of land communities, letters and complaints to authorities required the use of methods of systematization, typology and classification. The scientific novelty. Justification of the concept of the organization and activities of the Institute of the Land Community of the Dnieper Ukraine, the essence of which is that the Institute of the Land Community of the Dnieper Ukraine in 1917–1930 was based on the historical traditions of the Ukrainian people; was a self-governing, self-regulating organization; played a significant role in the economic and social life of the village. The experience of the land community can be used to preserve the peasantry as a stratum of Ukrainian society. The experience of land communities in the process of dividing and organizing land will be useful in the conditions of the introduction of the land market in modern Ukraine. Conclusions. During the land management, the peasants gained the opportunity to correct the shortcomings of traditional forms of land use, which led to a noticeable decrease in cross-strip and distant land in peasant farms. The elimination of negative factors of land management created favorable conditions for the reorganization and intensification of peasant farms. Improved crop rotations were introduced, the areas of intensive crops increased, which had a positive effect on productivity